Supraclavicular Approach on Thoracic Outlet Syndrome - Amiril Mu’imin (Neurologico Spinale Medico Chirurgico, 2018)
Background: Thoracic Outlet Syndrome (TOS) is a clinical syndrome that refers to abnormal compression of the neurovascular in the neck and axilla with signs and symptoms manifesting in the shoulders, neck, arms, hands and sometimes fingers. It may be underdiagnosed because this syndrome is poorly understood. The compression is primarily neurogenic, vascular, or both. As the number of patients undergoing successful treatment increases, TOS is becoming a common diagnosis. In those patients in whom pain is refractory to conservative care, surgery should be considered. The aim of this study is to evaluate the outcome of a supraclavicular approach to treat the thoracic outlet syndrome patients in Dr. Ramelan Navy Hospital Surabaya. Materials and methods: This study is a case series of 16 patients (10 females and 6 males) of 19-50 years old, who underwent neurovascular compression with the supraclavicular approach. Symptoms were evaluated with medical records based on peri-operative anamnesis and physical examination. Results: The follow-up with 16 patients showed excellent results such as decreasing pain, decreasing sensory or motoric symptoms, and complications like pneumothorax hematothorax, and injury of artery, vein or plexus brachialis were not found. Conclusion: Supraclavicular approach is relatively effective and safe for neurovascular decompression of TOS. Excellent outcomes were observed with a small incision, safe and minimal complications.